2021
DOI: 10.2147/cmar.s313013
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the Time Interval Between Primary Debulking Surgery and Start of Adjuvant Chemotherapy in Advanced Epithelial Ovarian Cancer

Abstract: Aim: To investigate whether the time interval between primary debulking surgery (PDS) and initiating adjuvant chemotherapy affects survival in patients with epithelial ovarian cancer (EOC). Methods: We retrospectively reviewed FIGO stage IIB to IV EOC patients who received PDS followed by adjuvant chemotherapy in our hospital between January 2008 and December 2016. The optimal cut-off time interval to chemotherapy related to survival was determined using the Contal and O'Quigley method and Cox hazard models. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Generally, it is recommended to start or resume chemotherapy as soon as possible after cytoreductive surgery. Several studies have shown that initiating adjuvant chemotherapy >42 days after cytoreduction is independently associated with adverse survival outcomes [ 10 , 11 , 12 ]. A recent study demonstrated that women with TTC ≤ 42 days had a significantly better median progression-free survival (PFS) compared to those with TTC > 42 days (35.5 vs. 22.6 months) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is recommended to start or resume chemotherapy as soon as possible after cytoreductive surgery. Several studies have shown that initiating adjuvant chemotherapy >42 days after cytoreduction is independently associated with adverse survival outcomes [ 10 , 11 , 12 ]. A recent study demonstrated that women with TTC ≤ 42 days had a significantly better median progression-free survival (PFS) compared to those with TTC > 42 days (35.5 vs. 22.6 months) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that initiating adjuvant chemotherapy >42 days after cytoreduction is independently associated with adverse survival outcomes [ 10 , 11 , 12 ]. A recent study demonstrated that women with TTC ≤ 42 days had a significantly better median progression-free survival (PFS) compared to those with TTC > 42 days (35.5 vs. 22.6 months) [ 10 ]. A meta-analysis in patients with International Federation of Gynecology and Obstetrics (FIGO) stage III–IV showed that overall survival (OS) declined by 4% for each week that adjuvant chemotherapy was delayed [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to research conducted in Nigeria and Africa, ovarian cancer ranks as the second most common gynaecological cancer, comprising approximately 7 to 8.2% of all gynecological malignancies [2]. Unfortunately, around 75% of cases are diagnosed at advanced stages, which can be attributed to the absence of specific clinical manifestations and effective screening methods [3,4]. The survival rate of patients with ovarian cancer is highly dependent on the stage at diagnosis.…”
Section: Introductionmentioning
confidence: 99%